The Impact of Digital Marketing Strategies and Environmentally Friendly Innovations on Brand Loyalty at The Body Shop Thamrin Plaza: Dampak Strategi Pemasaran Digital dan Inovasi Ramah Lingkungan terhadap Loyalitas Merek di The Body Shop Thamrin Plaza - Anjeli; Hommy Dorthy Ellyany Sinaga (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2025)
This research is motivated by the low levels of customer involvement and loyalty at The Body Shop Thamrin Plaza Medan, despite the outlet implementing promotions, various programs, and recycling workshops. To address this issue, the study employs a quantitative approach with a sample of 100 customers selected using incidental (convenience) sampling through a structured questionnaire. The data were tested for validity and reliability, were found to meet the classical assumptions of normality and multicollinearity, and were then analyzed using multiple linear regression on SPSS version 25. The t-test shows that digital marketing strategies have a significant positive effect on brand loyalty (β = 0.408, t = 4.703, p < 0.05) while environmentally friendly innovations also have a significant positive effect (β = 0.456, t = 4.765, p < 0.05). The overall F test indicates that both variables collectively explain 58.8% of the variation in brand loyalty (F = 69.278, p < 0.05). These results support all three hypotheses and recommend enhancing digital content personalization as well as regularly scheduling green programs to strengthen relationships with consumers and potentially increase brand loyalty for The Body Shop Thamrin Plaza Medan.